2020
DOI: 10.1101/2020.09.28.317578
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The novel anti-CRISPR AcrIIA22 relieves DNA torsion in target plasmids and impairs SpyCas9 activity

Abstract: To overcome CRISPR-Cas defense systems, many phages and mobile genetic elements encode CRISPR-Cas inhibitors called anti-CRISPRs (Acrs). Nearly all mechanistically characterized Acrs directly bind their cognate Cas protein to inactivate CRISPR immunity. Here, we describe AcrIIA22, an unconventional Acr found in hypervariable genomic regions of Clostridial bacteria and their prophages from the human gut microbiome. Uncovered in a functional metagenomic selection, AcrIIA22 does not bind strongly to SpyCas9 but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 99 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…The strongly reduced target recognition efficiency in absence of supercoiling suggests that CRISPR-Cas systems have evolutionary been optimized to support efficient recognition of invaders with supercoiled DNA. This is supported by the discovery of a novel anti-CRISPR protein, which nicks plasmid DNA to release supercoils in order to strongly reduce the targeting efficiency of CRISPR-Cas9 55 as well as the torque-dependent post-cleavage behavior of Cas9 itself 56 . The genomes of eukaryotic cells are however considerably less supercoiled than prokaryotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…The strongly reduced target recognition efficiency in absence of supercoiling suggests that CRISPR-Cas systems have evolutionary been optimized to support efficient recognition of invaders with supercoiled DNA. This is supported by the discovery of a novel anti-CRISPR protein, which nicks plasmid DNA to release supercoils in order to strongly reduce the targeting efficiency of CRISPR-Cas9 55 as well as the torque-dependent post-cleavage behavior of Cas9 itself 56 . The genomes of eukaryotic cells are however considerably less supercoiled than prokaryotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…and 5 Acr proteins against the subtype II-C CRISPR-Cas system. [18][19][20] Structural and mechanistic studies revealed that type II Acrs inhibit their host Cas9 proteins through diverse mechanisms. They occupy the protospacer adjacent motif interaction site of Cas9 to compete with target DNA binding, 21,22 block the active site of the Cas9 nuclease domain, 23 induce nonfunctional Cas9 dimerization, 24,25 and cause Cas9 degradation in cell culture.…”
Section: Self-association and Interaction Of Acriic2mentioning
confidence: 99%